Predictive factors for treatment failure in patients with presumed ocular tuberculosis in an area of low endemic prevalence. Issue 3 (17th July 2015) - Agrawal, Rupesh; Gonzalez-Lopez, Julio J; Nobre-Cardoso, João; Gupta, Bhaskar; Grant, Robert; Addison, Peter KF; Westcott, Mark; Pavesio, Carlos E
Abstract : Aim: To assess the impact of antitubercular therapy (ATT), oral steroids and steroid sparing immunosuppressive treatment on treatment success in cases with presumed ocular tuberculosis in an area of low endemic prevalence. Methods: A retrospective cross-sectional study was performed for 213 patients with presumed ocular tuberculosis from a database from a tertiary referral eye hospital in the UK. A logistic regression model was constructed incorporating demographics, baseline characteristics and different cut-offs of QuantiFERON-TB Gold In-Tube test (QFT-G) to identify significant factors accounting for the variability of the response variable ('failure') across the whole group. Treatment failure was defined as the recurrence of inflammation or inability to taper steroids within 6 months of completion of ATT or after at least 6 months of treatment in the non-ATT group. Results: There were 126 patients who had at least 6 months of ATT. Patients with QFT-G values >1.50 (OR=0.20, 95% CI 0.09 to 0.48, p<0.001) had less risk of treatment failure as against those with QFT-G values between 0.35 and 1.50. Steroid sparing immunosuppressive agents reduced the chances of treatment success (OR=24.10, 95% CI 6.75 to 86.11, p<0.001). This effect persisted even after adjusting for potential confounding factors. Conclusions: Patients with higher values of QFT-G (>1.5) are more likely to have treatment success with ATT. In our model, steroid sparing immunosuppressive agents reduced the chances of success in both ATT and non-ATT-treated patients. It is unclear whether this effect reflects the intrinsic underlying severity of disease (ie, study bias), or whether steroid sparing immunosuppressive agents mitigate against successful ATT.